Formation of transdisciplinary competences in doctors - Krasnov, Volodymyr; Shcherbinska, Olena; Sichkoriz, Orest (ScienceRise: Pedagogical Education, 2017)
During the third millennium the humanity faced the multilevel problems. Their solutions require specialists with new level of thinking. All the attempts to solve these problems on transdisciplinary level do not give the appropriate result, because usually specialists don’t go further beyond the boundaries of their subject areas. Since 1970 the transdisc pi inary approach has been developed, within the framework of which the scientific worldview is expanding, and problems are considered at several levels simultaneously without limitation, by the limits of any one scientific discipline. However, the methods of transdisciplinary competences forming in specialists still remain unclear. The authors suggested the usage of a group “circle” approach in the training of practicing doctors and interns, who are trained at the stages of postgraduate medical education and continuous professional development. The condition of pedagogical technology is that experts (lecturers) from different subject areas and trainees (doctors-specialists), collaborate while solving the problems. Within the “circle” the situation is analyzed on the physical, legal and psy chological levels and the search for the most optimal solutions is performed. At the same time, doctors, Methodists, lawyers and psychologists create a common, transdisciplinary space that provides self-learning and mutual learning of all the participants. As a result: 1) The technology of group induing ‘circle method ’ is offered ai joint paroopanoo of experts of a different profile: 2) In the course of the wort participants significant expanded the horizons of their own knowledge: 3) The acquired skills enabled specialists to use the group method subsequently for integrating cognitive spaces and finding the causes of emerging problems at different levels.